AN INVESTIGATION OF INTERACTION AMONG WILLINGNESS TO COMMUNICATE, ACADEMIC ACHIEVEMENT AND L2- SELF GUIDES - Mirici, Ismail Hakki; Sari, Seyda (International Online Journal of Education and Teaching, 2021)
In this quantitative study, which utilized focus group survey method, the relationship among anxiety (specifically speaking anxiety in classroom), ideal L2-self and willingness to communicate was explored. The participants of the study were selected using convenience sampling model, and were composed of 81 volunteer students in total (26 females, 55 males) at a state university in Turkey in 2017-2018 academic year. The data were collected via; a) Ideal L2-self Scale (Dörnyei & Taguchi, 2010). The internal consistency of the scale was α = .90; b) Willingness to Communicate Scale (WTC) (Mccroskey, 1992) The internal consistency of the scale was Α = .94; and c) Foreign language speaking anxiety scale (FLSAS) by Huang (2004). The data were analyzed using the SPSS 21.00 software, and Pearson Correlation Analysis and Regression Analysis were conducted to find out whether Speaking Anxiety, Ideal L2-Self and Participants’ GPA predict WTC. The results revealed that Ideal L2-Self didn’t really affect students WTC (Beta=0.192, t=1.648; p=0.104>0.05). However, students’ GPA significantly affected their WTC (Beta=0.243, t=2.087; p=0.040<0.05).